Determination of cost-effective optimum coagulant dosage for removal of disinfection by-product precursors in water treatment based on the theory of elasticity. (June 2022) - Li, Wei; Wang, Junqi; Xin, Huiyu; Li, Ting; Duan, Jinming; Mulcahy, Dennis
Abstract: Determination of coagulant dosage in drinking water treatment is related to the requirements for drinking water quality as well as the treatment costs. Selection of appropriate coagulant dosages has been an issue for water treatment utilities, though empirical approaches were normally considered or employed. Inspired by the theory of elasticity in microeconomics, this study explored a novel approach for the cost-effective optimum coagulant dosage. This could enable water utilities to achieve the maximum possible removal efficiency of precursors for disinfection byproducts (DBPs) while maintain an economical dosage without incurring an excessive cost. The relationships between DBP formation potential (DBPFP) and several relevant water quality parameters were first examined and evaluated. UV254 was found the most appropriate DBPFP indicator with the highest correlation coefficients. Based on the relationship of UV254 and DBPFP, an approach for determination of cost-effective optimum coagulant dosage was delineated. The results showed that use of the cost-effective optimum coagulant dosage, which account for approximately 33% of optimum coagulant dosage, could achieve 79% of maximum removal efficiencies of UV254 for the source waters tested, thereby substantially reducing the formation of DBPs. Further increase the coagulant dosage was believed uneconomical since the increase in UV254 removal was limited. Similar results were obtained with different coagulants and with raw water samples with diverse water qualities. The results suggest that the proposed approach could provide a mathematical tool for cost-effective optimum coagulant dosage control which could at the same time achieve sufficient removal of natural organic matter to reduce DBPs formation. Highlights: A new concept of cost-effective optimum dose is proposed based on elasticity theory. Comparative analysis on correlation of NOM surrogates with DBPFP is provided. UV254 can serve as a good DBPFP indicator during conventional water treatment. A mathematical tool for coagulant optimization for DBPs control is proposed. This method is applicable to different conditions of coagulants and source waters.